2016
DOI: 10.1097/rlu.0000000000001011
|View full text |Cite
|
Sign up to set email alerts
|

Immunoscintigraphy With 99mTc-Nimotuzumab for Planning Immunotherapy in Patients With Bone Metastases Due to Prostate Cancer

Abstract: Detection of bone metastases indicates poor prognosis for patients with prostate cancer. The immunotherapy with monoclonal antibody has been an important advance in the treatment of the cancer in the last years. Nimotuzumab is a humanized IgG1 monoclonal antibody directed against epidermal growth factor receptor that has been evaluated in solid tumors. The authors show images of 2 patients with bone metastases secondary to prostate cancer, "pre-cold therapy" with nimotuzumab. Immunoscintigraphic images were ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…6 Previous studies have demonstrated the anti-cancer effects of nimotuzumab in various types of cancers, including advanced head and neck cancer, 7 nasopharyngeal carcinoma, 8 esophageal squamous cell cancer, 9 as well as PCa. 10 Furthermore, in combination with oxidized tea polyphenols, nimotuzumab has shown enhanced inhibition of EGFR and tumor growth in non-small cell lung cancer cells and tumor-bearing mice. 11 Additionally, Hu et al revealed that nimotuzumab can markedly suppress malignant behaviors in PCa cell lines, such as epithelial-mesenchymal transition (EMT), invasion, migration, and proliferation.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…6 Previous studies have demonstrated the anti-cancer effects of nimotuzumab in various types of cancers, including advanced head and neck cancer, 7 nasopharyngeal carcinoma, 8 esophageal squamous cell cancer, 9 as well as PCa. 10 Furthermore, in combination with oxidized tea polyphenols, nimotuzumab has shown enhanced inhibition of EGFR and tumor growth in non-small cell lung cancer cells and tumor-bearing mice. 11 Additionally, Hu et al revealed that nimotuzumab can markedly suppress malignant behaviors in PCa cell lines, such as epithelial-mesenchymal transition (EMT), invasion, migration, and proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Its mechanism of action involves competing with other specific ligands to target epidermal growth factor receptor (EGFR, effectively suppressing cancer development 6 . Previous studies have demonstrated the anti‐cancer effects of nimotuzumab in various types of cancers, including advanced head and neck cancer, 7 nasopharyngeal carcinoma, 8 esophageal squamous cell cancer, 9 as well as PCa 10 . Furthermore, in combination with oxidized tea polyphenols, nimotuzumab has shown enhanced inhibition of EGFR and tumor growth in non‐small cell lung cancer cells and tumor‐bearing mice 11 .…”
Section: Introductionmentioning
confidence: 99%
“…A recent case report showed that nimotuzumab reduced prostate‐specific antigen (PSA) level in a patient with both PC and colon cancer . Another study on two PC patients presenting bone metastasis reported metastasis‐inhibitory effect of nimotuzumab . Yet few studies have comprehensively examined the therapeutic efficacy of nimotuzumab in PC.…”
Section: Introductionmentioning
confidence: 99%
“…Nimotuzumab (hR3) is a humanized IgG1 monoclonal antibody directed against epidermal growth factor receptor (EGFr) [1][2][3][4]. It has potent anti-proliferative, antiangiogenic, and pro-apoptotic effects in vitro and in vivo.…”
mentioning
confidence: 99%